D’un continent a l’autre : la littérature comme une arme du combat féminin - Kindo, Aïssata Soumana (2018)
Although they may be the produce of different context and environment, Calixthe Beyala et Lalita Tademy, two famous black women novelists, respectively from Africa and USA, join in the same fight beyond continents through the themes they develop, the characters they present and their styles (writings), which is almost contrary. For African women writers, literature is not only an act of recovering women’s speech, for so long confiscated, but also a way to face, in many ways, male power and male society. The literary protagonists of African feminism just wish to keep distant from family, where young girls’ alienation and domestication have occurred for centuries. They break the myth of the admirable mother, celebrated by the Négritude movement, for it perpetuates alienating practices, among which excision. They condemn patriarchal order which deny their existence, stand for the right of selfmanagement. Afro-American women writers, on the on hand, have pointed out slavery and its consequences, then Afro-American life conditions in general and Afro-American women in particular in racism context. Nowadays, Afro-American women writers bring new narrative trends, namely as far as slavery history is concerned. They speak about new places, new city neighbourhoods, new schools, new friends, new working places, and describe new experiences which are clearly illustrated in the novels by Terry Mc Millan, Andrea Lee, Connie Porter or Tonni Morrison. In order to consider better this women struggle, we propose to study two of theses writers’ works that exemplify this new tendency in women’s literature in Africa and USA: Seul le DIABLE le savait by Calixthe Beyala and Au bord de la rivière Cane by Lalita Tademy.